Characteristics of Discourses of Helping Professions - I. V. Shugaylo (Дискурс, 2025)
Introduction. The article examines the role of an agent of therapeutic influence and analyzes the features of discourses of helping professions (with their agents: psychologist, psychotherapist, doctor, teacher, shaman, lawyer) in modern therapeutic practices with clients in situations of various types of assistance. The purpose of this article is to analyze the varieties of the language of discourses of helping professions. The Russian linguist V.I. Karasik distinguishes medical discourse in the institutional discourses, and considers psychotherapeutic one as its variety. Meanwhile, at the present stage of the development of discourse analysis, it is possible to supplement some tactics and linguistic approaches to clients in the discourses of helping professions (DHP) in connection with the new paradigm of natural sciences – the complex consideration of a man as a biosocial, mass, cosmic being. Hence, therapists show the deep interest in the most ancient archaic types of discourse – magical, meditative, religious, etc.Methodology and sources. The article is based on the main provisions of the theories of V.I. Karasik and Ten van Dijk. The methodological basis of the analysis carried out in the article were scientific works that deal with psychotherapeutic discourse (A.R. Markin, M.S. Grineva, E.V. Ermolaeva), medical one (M. Foucault, V.V. Zhura, O.A. Shesterikova, V.G. Silantieva), law discourse (M. Foucault, V.G. Ishchenko, M.S. Medvedeva, S.A. Zimina), pedagogical (E.T. Bulgakova, K.A. Vospishcheva, L.M. Osinovskaya), magical (G. Storms and F. Grandon, E.G. Ermolaeva, M.L. Cameron), meditative (M.G. Eremchenko, O.A. Dmitrieva, E.N. Melnikova).Results and discussion. The article characterizes and highlights the specifics of various DHP, describes the features of language techniques that used in these discourses, depending on the goals of influencing the client.Conclusion. The study shows the specifics of the DHP, primarily related to the goals and objectives in different cultures and ambiguous situations of therapeutic practice.